Prevalence Of Depression And Associated Factors Among Elderly Population In A Rural Area Of Kozhikode District, North Kerala. - Roshni SS; MP, Lilabi; JS, Krishna Raj; Bindu V; Ageesh TG (National Journal of Community Medicine, 2023)
Background: Old age is often accompanied by frailty and diseases including neuropsychiatric disorders. Demen-tia and depression are the most common neuropsychiatric disorders among the elderly. Kerala has the maximum proportion of elderly in its population and successful identification of the elderly at risk is important for early in-tervention. The purpose of the study is to estimate the prevalence of depression and associated factors among the elderly population. Methods: A cross-sectional study was conducted among 320 elderlies from July 2018 to July 2019.The preva-lence of depression was estimated using GDS-15. Socio-demographic factors, self- perceived health status, mor-bidity profile, falls and related factors, religious practices, independence in activities of daily living, and other so-cial factors associated with depression were assessed. Results: 38.1% of the elderly were depressed. Majority had mild depression (23.4%) and 3.1% were severely depressed. Having no formal education, low socioeconomic status, not living with a spouse, no role in decision -making, average or poor self-perceived health status, past surgical history, and fear of falls were found to be inde-pendent predictors of depression. Conclusion: The prevalence of depression was high among elderly. Screening for depression in the elderly should be incorporated in already available programs along with appropriate health care measures.